Analog Organic Electronics Building Blocks for Organic Smart Sensor Systems on Foil - Marien, Hagen; Steyaert, Michiel; Heremans, Paul (Analog Circuits and Signal Processing, 2013)
This book provides insight into organic electronics technology and in analog circuit techniques that can be used to increase the performance of both analog and digital organic circuits. It explores the domain of organic electronics technology for analog circuit applications, specifically smart sensor systems.  It focuses on all the building blocks in the data path of an organic sensor system between the sensor and the digital processing block. Sensors, amplifiers, analog-to-digital converters and DC-DC converters are discussed in detail. Coverage includes circuit techniques, circuit implementation, design decisions and measurement results of the building blocks described. Offers readers the first book to focus on analog organic circuit design; Discusses organic electronics technology for analog circuit applications in the context of smart sensor systems; Describes all building blocks necessary for an organic sensor system between the sensor and the digital processing block; Includes circuit techniques, circuit implementation, design decisions and measurement results.    .